Optimization, dynamics analyses and trajectory tracking of aircraft perching maneuvers - D. M. K. K. Venkateswara Rao (2015)
This thesis presents optimization, parametric study, stability analysis and trajectory tracking of fixed-wing aircraft perching maneuvers, where gravity and aerodynamics forces are used simultaneously for climbing to decelerate and land with low velocity or negligible impact. A single-phase formulation, which minimizes the trajectory length of the maneuver, is proposed to simplify the optimization formulation and generate lower undershoot perching solutions, compared with the existing two-phase approach. A parametric study is carried out to identify some of the key aircraft geometric features and parameters having significant influence on the maneuver. The aircraft parameters are varied and optimal perching solutions are computed from which their influence on the maneuver is identified. Aerodynamics from changing aircraft configurations due to parameter changes is modeled using nonlinear vortex correction method coupled with Wagner’s unsteady model. Stability analysis of the optimal perching trajectories is performed using contraction theory to analyze the effects of state perturbations. It is shown that the perching solutions are in general unstable and will diverge during the terminal phase. To avoid divergence, tracking of optimal trajectories is proposed. Sliding mode control technique is used to design the tracking controller, and its performance is validated through numerical simulations. The design of the controller is extended for tracking of a conventional aircraft landing maneuver by including lateral states into the model. The design of the controller is validated through numerical simulations, and its performance is compared with a PID controller.